Un plein panier d'aliments pour l'Afrique d'ici 2020 (International Food Policy Research Institute, 2004)
The poems, stories, and essays in this booklet are selected entries from an Africa-wide youth writing contest on the theme: "A full food basket for Africa by 2020 / Un plein panier d'aliments pour l'Afrique d'ici 2020." Sponsored by IFPRI's 2020 Vision Initiative, the contest was organized in preparation for the all-Africa conference, "Assuring food and nutrition security in Africa by 2020: prioritizing actions, strengthening actors, and facilitating partnerships" held in Kampala, Uganda, 1-3 April 2004.